PERAN GURU KRISTEN DALAM MENDIDIK KARAKTER KESANTUNAN BERBAHASA SISWA BERDASARKAN TINJAUAN FILSAFAT ETIKA KRISTEN [THE ROLE OF CHRISTIAN TEACHER IN EDUCATING STUDENTS’ LANGUAGE CHARACTER BASED ON CHRISTIAN ETHICS PHILOSOPHY] - Pitaya Rahmadi; Meyviane Pricilia Gloria (Polyglot, 2021)
The character of students in class can be shown through the attitude of talking to others. The politeness of using the language is something that must be considered when someone interacts. However, the facts that occur in the world of education show that there are still students and teachers who do not pay attention to the politeness of the language while the lesson is taking place. This shows the lack of awareness of educators to apply and educate the character of students' politeness in the class. The purpose of this paper is to explain the important role of Christian teachers in educating the character of politeness in students' language use based on a review of Christian ethical philosophy. This writing is reviewed using the literature review method. The teachers as the example of morals, ethical mentors, and effective givers are responsible for educating the character of students holistically, in fulfilling God's calling to clarify the values of God's giving to the lives of each student. The politeness of the language is one realization of obedience to an ethic. Christian teachers need to have perspectives that refer to truth to avoid moral relativism. Through this perspective, the teachers are able to help students to have the right motivation in applying politeness in language, which are the response to the salvation of Christ and the tools for them to grow more like Christ. Suggestions for the teacher, it is better to develop sensitivity to the condition of students 'politeness of the language use and explore the principle of the language use politeness, and innovative ways to educate the character of students’ politeness in using the language.BAHASA INDONESIA ABSTRACT: Karakter siswa di kelas dapat ditunjukkan melalui sikap berbicara dengan orang lain. Kesantunan berbahasa menjadi hal yang harus diperhatikan ketika seseorang melakukan interaksi. Namun, fakta yang terjadi di dunia pendidikan menunjukkan masih terdapat siswa dan guru yang tidak memperhatikan kesantunan berbahasa saat pelajaran tengah berlangsung. Hal ini menunjukkan kurangnya kesadaran pendidik untuk menerapkan serta mendidik karakter kesantunan berbahasa siswa di kelas. Tujuan dari penulisan ini adalah menjelaskan pentingnya peran guru Kristen dalam mendidik karakter kesantunan berbahasa siswa berdasarkan tinjauan filsafat etika Kristen. Penulisan ini dikaji menggunakan metode kajian literatur. Guru sebagai contoh moral, mentor etika, dan pemberi yang efektif bertanggung jawab untuk mendidik karakter siswa secara holistis, dalam memenuhi panggilan Tuhan untuk memperjelas nilai-nilai pemberian Tuhan kepada kehidupan setiap siswa. Kesantunan berbahasa merupakan salah satu realisasi dari kepatuhan akan suatu etika. Guru Kristen perlu memiliki perspektif yang mengacu pada kebenaran untuk menghindari relativisme moral. Melalui perspektif tersebut, guru mampu menolong siswa untuk memiliki motivasi yang tepat dalam menerapkan kesantunan berbahasa, yakni sebagai tanggapan terhadap keselamatan Kristus serta sarana untuk mereka bertumbuh semakin menyerupai Kristus. Saran terhadap guru, sebaiknya perlu menumbuhkan kepekaan akan kondisi kesantunan berbahasa siswa dan mengeksplorasi prinsip kesantunan berbahasa, serta cara-cara inovatif untuk mendidik karakter kesantunan berbahasa siswa.